Експресија на CD133 и CD44 како стем-клетка маркери кај колоректален карцином - Костовски, Огнен (Медицински факултет, УКИМ, Скопје, 2017)
Introduction In the Western world, the incidence of colorectal carcinoma is in the third place in women after breast and lung carcinoma and also in men after lung and prostate carcinoma. The most important risk factor for development of colorectal carcinoma is age: 99 percent of cases of colorectal carcinoma are found in patients above 40 years of age and 85% of them are older than 60 years. Aims The primary goal is to determine the differences in the expression of colorectal cancerous cell markers that are the object of research in this PhD thesis in both selected subgroups of patients with metastatic and non-metastatic clinical form, as well as their correlation with other clinical, histopathologic and anatomical covariates. Materials and methods Ninety patients with colorectal carcinoma from the Clinic for Digestive Surgery, Clinical Centar “Mother Teresa”– Skopje, were selected for this study. Tumor samples were analyzed with standard histopathologic methods, and afterwords immunohistochemical analysis with monoclonal antibodies directed towards CD133 and CD44, was performed at the Institute of Pathology, Medical Faculty – Skopje, UKiM, Skopje. Results In our study, high coexpression of markers CD133 and CD44 (CD133/CD44) was observed in 71.4% of patients with metastatic disease, compared to 37.9% in patients without distant metastases. In this case, discordant expression of the two markers was found in 8% (n = 2) of the group with distant metastases, and in the group without distant metastases the percentage was 13.4% (n = 9). Statistical analyses has shown that there is a significant association of increased expression of CD133 and CD44 with the disease stage, T - category and N - nodal status, of which the stage of the disease has the highest statistically significant association with the expression of CD133 and CD44. Conclusion With multiple regression analysis, the stage of the disease was singled out as the factor with the greatest and statistically significant influence on the expression of CD133 (p <0.0001) and on the expression of CD44 (p <0.0001). Our results suggest that the expression of CD133 and CD44 can play an important role in isolating a potential subgroup of patients with a clinically aggressive form of disease, and the coexpression of these two markers is routinely implemented in standard pathohistological diagnostics and represents pre-therapeutic oncology screening.
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Никола Јанкуловски.
Keywords: colorectal carcinoma, stem cells, CD133+, CD44+